Numerical investigation of floating zone silicon using Halbach array magnets - Han, Xue-Feng; Kakimoto, Koichi; Alradi, Samah; Zaidat, Kader (Journal of Crystal Growth, 2020)
•The application of Halbach array magnets for FZ process is proposed.•Magnetic field in the melt provided by Halbach array magnets is adequately strong.•Halbach array magnets can locally restrain the melt flow.•Halbach array magnets can improve the crystallization interface deflection. Novel applications of Halbach array magnets in floating zone processes are proposed. Calculations of the floating zone process with two designs of Halbach array magnets are carried out and compared with the conventional floating zone process. The first part of the calculations including the static and high-frequency electromagnetic fields in the melt and crystal are modelled in COMSOL software. The effect of electromagnetic fields on the melt flow is calculated in three dimensions. From the calculation results, we confirm that Halbach array magnets can provide an adequately strong magnetic field at the surface of silicon to affect the melt flow. From the comparison of calculation results between conventional floating zone and floating zone with Halbach array magnets, the effects of the magnetic field on the melt flow, the temperature distribution, and the crystallization interface are confirmed. Halbach array magnets can locally restrain the melt flow velocity and improve the deflection of the crystallization interface.